Some Aspects Of The Project On Education In Business Administration For Negros - Unterman, Israel (Academy of Management Journal, 1970)
Schools of business, in keeping with the changing environment of higher education, are endeavoring to educate black and white students in minority problems affecting business management. When new activities have been tried, an area of misunderstanding has occurred between the black community and the white academicians. The difference stems from the lack of knowledge of the dynamics of ghetto economics and a conflict in cultural value systems between white middle class professors and black students and businessmen. Where faculty and administrators have recognized the differences in attitudes and values, and where faculty agrees to change, it may be necessary to alter the operational system of the school as well as change some of the criteria of management education.